2012
DOI: 10.1038/ejhg.2012.46
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide search for linkage to allergic rhinitis in Danish sib-pair families

Abstract: Allergic rhinitis (AR) is a complex disorder with a polygenic, multifactorial aetiology. Twin studies have found the genetic contribution to be substantial. We collected and clinically characterised a sample consisting of 127 Danish nuclear families with at least two siblings suffering from AR or allergic conjunctivitis including 540 individuals (286 children and 254 parents). A whole-genome linkage scan, using 424 microsatellite markers, was performed on both this sample and an earlier collected sample consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our group has implemented the MOD score approach, including a routine to perform simulations under the null hypothesis of no linkage, in the GENEHUNTER-MODSCORE (GHM) software (Brugger & Strauch, 2014;Dietter et al, 2007;Mattheisen et al, 2008;Strauch, 2003), which is based on the GENEHUNTER program (Kruglyak et al, 1996). Its application has led to the identification of a variety of genetic disease loci responsible for congenital heart defects (Flaquer et al, 2013), allergic rhinitis (Kruse et al, 2012), atopic dermatitis (Christensen et al, 2009), bipolar affective disorder (Schumacher et al, 2005), and house dust mite allergy (Kurz et al, 2005). Nonparametric linkage methods have been proposed as an alternative to parametric analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has implemented the MOD score approach, including a routine to perform simulations under the null hypothesis of no linkage, in the GENEHUNTER-MODSCORE (GHM) software (Brugger & Strauch, 2014;Dietter et al, 2007;Mattheisen et al, 2008;Strauch, 2003), which is based on the GENEHUNTER program (Kruglyak et al, 1996). Its application has led to the identification of a variety of genetic disease loci responsible for congenital heart defects (Flaquer et al, 2013), allergic rhinitis (Kruse et al, 2012), atopic dermatitis (Christensen et al, 2009), bipolar affective disorder (Schumacher et al, 2005), and house dust mite allergy (Kurz et al, 2005). Nonparametric linkage methods have been proposed as an alternative to parametric analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, multiple linkage studies were performed for AD (summarized in Ref . 24 ) and AR 2529 . It was frequently observed that loci overlapped across associated traits; for example, Daniels and colleagues observed overlapping linkage peaks with quantitative traits associated with asthma including total serum IgE, skin test index, and eosinophil counts, as well as atopy as a qualitative trait 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Our group has implemented the MOD-score approach, including a routine to perform simulations under the null hypothesis, in the GENEHUNTER-MODSCORE (GHM) software [10][11][12][13] . Its application has led to the identification of a variety of genetic disease loci [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%